Foodborne Botulism Outbreaks in the United States, 2001–2017 - Lúquez, Carolina; Edwards, Leslie; Griffin, Chelsey; Sobel, Jeremy (Frontiers in Microbiology, 2021)
Foodborne botulism is an intoxication caused by ingestion of food containing botulinum neurotoxin. Cases of foodborne botulism are usually sporadic (single, unrelated) but outbreaks of two or more cases occur. In this mini-review we will examine the following for the period 2001-2017, in the United States: botulism surveillance data, outbreaks of botulism affecting 10 or more people, and the public health preparedness and response approach.